Comparison of isolated tenotomy vs. tenotomy with tenodesis for long head of biceps tendon in middle-aged and elderly patients undergoing rotator cuff repair: a retrospective study - Ma, Ning; Chen, Xinghua; Pan, Chenshuai; Xie, Zonggang (Frontiers in Surgery, 2026)
PurposeRotator cuff tears (RCTs) are a prevalent source of shoulder disability, frequently accompanied by pathologies of the long head of the biceps tendon (LHBT). While both tenotomy and tenodesis are established procedures for managing LHBT lesions during rotator cuff repair, their comparative efficacy remains a subject of debate. This study aimed to compare the clinical outcomes of isolated tenotomy vs. tenotomy with tenodesis in patients undergoing arthroscopic RCTs in a retrospective study.MethodsAll surgical procedures involved arthroscopic rotator cuff repair performed by a single surgeon. Patients were divided into isolated biceps tenotomy and tenotomy with tenodesis using a suture anchor. Postoperative rehabilitation was standardized. Outcomes were assessed preoperatively and at 3, 6, 12 months, and final follow-up using ASES and Constant-Murley scores, VAS pain scale, operative time, and complications.ResultsA total of 63 patients (mean age 67.3 years) were retrospectively reviewed and divided into two groups: isolated tenotomy (n = 28) and tenotomy with tenodesis (n = 35). Preoperative demographics and functional scores (ASES, Constant-Murley, VAS) were comparable between groups. Both techniques resulted in significant and sustained improvements in all functional and pain outcomes at 3, 6, and 12 months postoperatively compared to baseline. In the early postoperative period (3 months), the tenotomy group demonstrated a statistically superior improvement in VAS pain scores. However, these differences in functional and pain scores between the two groups were no longer significant at the 6 and 12-month follow-ups. The operative time was significantly shorter for the tenotomy group. The only significant complication difference was the occurrence of Popeye deformity in two patients (14%) in the tenotomy group, with no cases in the tenodesis group.ConclusionIn conclusion, both isolated tenotomy and tenodesis provide equivalent, excellent functional improvements and pain relief at the 12-month follow-up. Tenotomy offers the advantages of a shorter operative time and better early pain control, at the cost of a higher risk of Popeye deformity. Tenodesis effectively prevents this cosmetic complication but requires a longer surgery.